2010
DOI: 10.1016/j.apenergy.2009.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Shower water heat recovery in high-rise residential buildings of Hong Kong

Abstract: This paper investigates the potential for shower water heat recovery from bathrooms equipped with instantaneous water heaters in high-rise residential buildings of Hong Kong. A simple single-pass counter-flow heat exchanger installed horizontally beneath the shower drain is employed as a localized heat recovery measure for preheating cold water going to a water heater. The thermal energy exchange is evaluated using the effectiveness-number of 32 transfer units (ε-NTU) approach. Shower usage patterns including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(81 citation statements)
references
References 28 publications
5
75
0
1
Order By: Relevance
“…The maximum CO2 reduction calculated from all of the measures listed in Table 2 using Equation (19) is estimated to be 52%. Table 2 summarizes the maximum CO 2 reduction estimates from various measures, including water conservation programmes that target P sh,35 ≥ 0.5 and T sf ≤ 5 • C, water efficient products, shower drain water heat recovery, and energy efficiency improvements for water supply systems [11,12,16,17]. The influence of users on CO 2 reduction is found to be significant and compatible to that of water efficient showerheads.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum CO2 reduction calculated from all of the measures listed in Table 2 using Equation (19) is estimated to be 52%. Table 2 summarizes the maximum CO 2 reduction estimates from various measures, including water conservation programmes that target P sh,35 ≥ 0.5 and T sf ≤ 5 • C, water efficient products, shower drain water heat recovery, and energy efficiency improvements for water supply systems [11,12,16,17]. The influence of users on CO 2 reduction is found to be significant and compatible to that of water efficient showerheads.…”
Section: Resultsmentioning
confidence: 99%
“…According to the survey, all occupants would take at least one shower per day [17]. A total of 597 occupants were interviewed; 269, 289, 37, and 2 of them would take one, two, three, and four showers in the summer while 537, 57, 3, and none of them would take one, two, three, and four showers in the winter respectively.…”
Section: Quantification For User Influencementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, its CO 2 emission would be only 76.9 ton yr −1 . Another study done by Wong et al (2010) also showed the high energy saving potential of a shower heat exchanger (Wong et al, 2010). They tested the efficiency of a horizontal shower heat exchanger, and estimated that an annual energy saving of 4-15 % can be achieved in a 40 floor (20 apartments per floor) high-rise residential building.…”
Section: Z Deng Et Al: Shower Heat Exchangermentioning
confidence: 99%
“…One of the most promising sources is the use of solar thermal energy for water heating proposed by Wong, Mui, & Guan (2010) and Altoé, Oliveira Filho and Carlo (2012).…”
Section: Introductionmentioning
confidence: 99%